Comparação físico-química e morfo-agronômica de genótipos de bananeira para cultivo nos tabuleiros costeiros de Sergipe - Silva, Tatiana Nascimento (2013)
The study of the physical and physico-chemical characteristics in the post-harvest of banana fruit contributes for the selection of the highlighted and adapted cultivars in the germoplasm implementation site. Therefore, this dissertation aims was to evaluate the quality of the cultivars and tree hybrids of banana post-harvest fruits, in two production cycles in Tabuleiros Costeiros, Sergipe, edaphoclimatic conditions, intending the material with superior characteristics selection for future recommendation. The experiment was conducted in Ecophysiology Laboratory at Embrapa Tabuleiros Costeiros, located in Aracaju-SE. The experimental design was made in randomized blocks with three repetitions, located in the Experimental Field Jorge do Prado Sobral at Embrapa Tabuleiros Costeiros in the city of Nossa Senhora das Dores, Sergipe, Tabuleiros Costeiros area. It were evaluated 12 agronomic characters in 13 banana tree genotypes coming from Rede Nacional de Avaliação de Genótipos de bananeira do Programa de Melhoramento da Embrapa (Nacional network for banana tree genotypes evaluation improvement program at Embrapa): Prata type (FHIA-18; PA42-44; PV94- 01; Garantida; YB42-47; Pacovan; Prata-Anã), Maçã type (Princesa; Tropical; Maçã), Caipira type (Caipira), Gros Michel type (Bucaneiro) Mysore type (Thap Maeo). The characters size, diameter and average weight of the fruits, pulp/skin relation, pH, total acidity titration, reducing sugars, total soluble solids, ratio, total sugars and amid were taken into consideration. The data underwent into variance analysis and the linear correlation between the characters evaluated took place. Using Gower algorithm, a dendrogram was elaborated with distance matrix obtained from agronomic, physic and physico-chemical fruit analysis in each cycle. Significant differences were noted for the fruit size variable, fruit diameter, fruit skin weight, fruit without skin weight, relation pulp/ skin, soluble-solids total content, total acidity titration and reducing sugars. With the genetic divergence used as a cut-off it was identified four groups in the second cycle: G1 group, formed by the genotypes FHIA-18, PA94-01, Caipira, YB42-47, Thap Maeo, Princesa, Tropical, Maçã and Pacovan; G2, by the genotypes PA42-44 and Prata Anã; G3, by the genotype Garantida and G4, by the genotype Bucaneiro. Four groups in the third cycle were also identified: G1, by the genotypes FHIA-18, PA42-44, PA94-01, Garantida, YB42-47, Thap Maeo, Prata Anã, Princesa, Maçã and Pacovan; G2, by the genotype Caipira; G3, by the genotype Tropical and G4, by the genotype Bucaneiro. The Bucaneiro genotype was qualified as promising to be incorporated by the production system of the banana producer in Sergipe. Total sugars, skin fruit weight, amid and fruit without skin weight characters contribute with a big part of the genetic variability between the 13 banana trees genotypes evaluated.